Growth response of syndromic versus non-syndromic children born small for gestational age (SGA) to growth hormone therapy: a Belgian study - Becker, Marianne; Thomas, Muriel; Brachet, Cécile; Heinrichs, Claudine; Dotremont, Hilde; De Schepper, Jean; Lysy, Philippe; Beckers, Dominique; , the BESPEED group; Rochtus, Anne; Parent, Anne-Simone; Klink, Daniel; et al. (Frontiers in Endocrinology, 2023)
Introduction: A substantial proportion of SGA patients present with a syndrome underlying their growth restriction. Most SGA cohorts comprise both syndromic and non-syndromic patients impeding delineation of the recombinant human growth hormone (rhGH) response. We present a detailed characterization of a SGA cohort and analyze rhGH response based on adult height (AH). Methods: Clinical and auxological data of SGA patients treated with rhGH, who had reached AH, were retrieved from BELGROW, a national database of all rhGH treated patients held by BESPEED (BElgian Society for PEdiatric Endocrinology and Diabetology). SGA patients were categorized in syndromic or non-syndromic patients. Results: 272 patients were included, 42 classified as syndromic (most frequent diagnosis (n=6): fetal alcohol syndrome and Silver-Russell syndrome). Compared with non-syndromic patients, syndromic were younger (years (median (P10/P90)) 7.43 (4.3/12.37) vs 10.21 (5.43/14.03), p=0.0005), shorter (height SDS -3.39 (-5.6/-2.62) vs -3.07 (-3.74/-2.62), p=0.0253) and thinner (BMI -1.70 (-3.67/0.04) vs -1.14 (-2.47/0.27) SDS, p=0.0054) at start of rhGH treatment. First year rhGH response was comparable (delta height SDS +0.54 (0.24/0.94) vs +0.56 (0.26/0.92), p=0.94). Growth pattern differed with syndromic patients having a higher prepubertal (SDS +1.26 vs +0.83, p=0.0048), but a lower pubertal height gain compared to the non-syndromic group (SDS -0.28 vs 0.44, p<0.0001). Mean rhGH dose was higher in syndromic SGA patients (mg/kg body weight/day 0.047 (0.039/0.064) vs 0.043 (0.035/0.056), p=0.0042). AH SDS was lower in syndromic SGA patients (-2.59 (-4.99/-1.57) vs -2.32 (-3.3/-1.2), p=0.0107). The majority in both groups remained short (<-2 SDS: syndromic 71%, non-syndromic 63%). Total height gain was comparable in both groups (delta height SDS +0.76 (-0.70/1.48) vs +0.86 (-0.12/1.86), p=0.41). Conclusions: Compared to non-syndromic SGA patients, syndromic SGA patients were shorter when starting rhGH therapy, started rhGH therapy earlier, and received a higher dose of rhGH. At AH, syndromic SGA patients were shorter than non-syndromic ones, but their height gain under rhGH therapy was comparable.